2015
DOI: 10.1136/gutjnl-2015-310101
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatumin colorectal carcinoma tissue and patient prognosis

Abstract: Objective Accumulating evidence links the intestinal microbiota and colorectal carcinogenesis. Fusobacterium nucleatum may promote colorectal tumour growth and inhibit T-cell-mediated immune responses against colorectal tumours. Thus, we hypothesized that the amount of Fusobacterium nucleatum in colorectal carcinoma might be associated with worse clinical outcome. Design We utilised molecular pathological epidemiology database of 1,069 rectal and colon cancer cases in the Nurses’ Health Study and the Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
786
5
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 807 publications
(864 citation statements)
references
References 53 publications
33
786
5
11
Order By: Relevance
“…During the past decade, an emerging notion that the contributions of the TME to carcinogenesis must be considered in the biology of neoplasms (16), revealing an important role of local tissue microenvironment involving in the formation of tumor-associated stroma in tumorigenesis. To date, several studies have found that altered tissue microenvironment has an effect on colorectal carcinogenesis, and epigenetic changes function as a key player in cellular response to the alteration of microenvironment (46)(47)(48), which are consistent with our results revealing the histologically altered morphologies of tissues with different distance to CRC lesions, loss of normal crypts and existence of many ACf in no. 3, however, tissues no.…”
Section: Discussionsupporting
confidence: 92%
“…During the past decade, an emerging notion that the contributions of the TME to carcinogenesis must be considered in the biology of neoplasms (16), revealing an important role of local tissue microenvironment involving in the formation of tumor-associated stroma in tumorigenesis. To date, several studies have found that altered tissue microenvironment has an effect on colorectal carcinogenesis, and epigenetic changes function as a key player in cellular response to the alteration of microenvironment (46)(47)(48), which are consistent with our results revealing the histologically altered morphologies of tissues with different distance to CRC lesions, loss of normal crypts and existence of many ACf in no. 3, however, tissues no.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, also bacterial species, such as Fusobacteria, reportedly associated with severe clinical outcome25 and that we found enriched in poorly infiltrated tumours, were capable to evoke expression of T cell recruiting chemokine genes by CRC cells in vitro. Further studies are warranted to clarify the final impact of individual bacterial species, and Fusobacteria in particular, on T cell function.…”
Section: Discussionmentioning
confidence: 63%
“…Two groups have recently shown that the abundance of F. nucleatum is gradually increased from normal tissues to adenoma tissues and to adenocarcinoma tissues in colorectal carcinogenesis (Castellarin et al, 2012; Kostic et al, 2012). Moreover, the amount of F. nucleatum in CRC tissues is associated with shorter survival (Mima et al, 2016). F. nucleatum adhesin FadA may bind to the E-cadherin protein and promote colorectal carcinogenesis (Rubinstein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%